Relief grating induced by photo-expansion in Ga-Ge-S and Ga-Ge-As-S glasses - Messaddeq, S. H.; Li, M. S.; Lezal, D.; Messaddeq, Younes [UNESP] (Natl Inst Optoelectronics, 2002)
We report the fabrication of relief diffraction gratings recorded on a surface of photosensitive Ga10Ge25S65 and Ga5Ge25As5S65 glasses by means of interference of two UV laser beams at 351 nm. The diffraction efficiency (eta) of first diffraction order was measured. Atomic-force-microscope (AFM) was used to perform a 3D imaging analysis of the sample surface topography that shows the superposition of an imprinted grating over the topography of the glass. The change in the absorption edge and the refractive index has been evaluated and a structural approach of the relief grating on the glass surface has been discussed.
Keywords: light-induced effects; chalcogenide glasses; relief gratings